2005
DOI: 10.1016/j.otohns.2004.09.072
|View full text |Cite
|
Sign up to set email alerts
|

Oral steroid regimens for idiopathic sudden sensorineural hearing loss

Abstract: B-3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0
6

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 18 publications
1
55
0
6
Order By: Relevance
“…Analysis of patients with slight hearing loss, on the other hand, did not demonstrate any remarkable differences in prognosis whether or not they received treatment [16] . Another retrospective review found that compared with patients who received low doses of glucocorticoids or who were treated later in their course, a better prognosis was detected in those who received high doses of prednisone (at least 60 mg/day) within 2 weeks after diagnosis [17] . In the current study, most patients (49/54, 91%) received oral prednisolone treatment within 2 weeks after the onset of SSNHL.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of patients with slight hearing loss, on the other hand, did not demonstrate any remarkable differences in prognosis whether or not they received treatment [16] . Another retrospective review found that compared with patients who received low doses of glucocorticoids or who were treated later in their course, a better prognosis was detected in those who received high doses of prednisone (at least 60 mg/day) within 2 weeks after diagnosis [17] . In the current study, most patients (49/54, 91%) received oral prednisolone treatment within 2 weeks after the onset of SSNHL.…”
Section: Discussionmentioning
confidence: 99%
“…1 Other studies have also shown the benefit of systemic corticosteroid therapy for hearing loss recovery in SSHL patients. 3,5,6,7,11 A few researchers, however, have published discouraging results as to the benefits of systemic corticosteroids compared to placebo. 2,4,8 The precise mechanism by which steroids may improve hearing remains unknown; both glucocorticoid and mineralocorticoid receptors may be found in the inner ear.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies, however, have suggested that patients with profound hearing loss have a worse prognosis. 2,7,11,24 The PTA of only one patient worsened (defined as any worsening in follow-up exams) after injections. Only this patient had a mildly worse SRR (defined as any worsening in follow-up exams) after injections.…”
Section: 50-52mentioning
confidence: 99%
“…Pacientams, sergantiems ŪINKP, buvo tiriami ir rasti pakitę šie parametrai: sumažėjęs CD3+, CD4+, CD8+ limfocitų skaičius, padidėjęs lygiųjų raumenų antikūnų kiekis, rasta antiendotelio ląstelių antikūnų, kryžminių reakcijų antikūnų (27,45,50,80 kd), nerasta antikūnų prieš skydliaukę ir branduolius [4, 16,53,54]. Kiti mokslininkai pacientams, sergantiems ŪINKP, rado antikūnų prieš lygiųjų raumenų struktūras ir autoantikūnų,…”
Section: Diskusijaunclassified
“…Taip pat pastebima, kad šiandieniniai gydymo metodai tapo invazyvūs, užtikrina medikamento patekimą į vidinę ausį. Manoma, kad vazodilatatoriai, vitaminai, steroidai, antikoaguliantai, histamino preparatai, diuretikai, prostaciklinai, hipervoleminė hemodiliucija, hiperbarinė oksigenacija, kiti gydymo metodai yra efektyvūs ir taikomi praktikoje tiek atskirai, tiek derinant keletą preparatų tarpusavyje [7,13,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Vis dėlto labai sudėtinga įvertinti įvairių medikamentų terapinį efektyvumą dėl to, kad skirtingų gydymo metodų terapinis efektyvumas prilygsta spontaninio pasveikimo dažniui (32-65%) [2,19,28,31].…”
unclassified